Kitchen garden, dietary diversity, and women’s health in rural eastern India: a mixed method study - Hazra, Shrobana; Parida, Swayam Pragyan; Giri, Prajna Paramita; Behera, Binod Kumar (Frontiers in Public Health, 2025)
BackgroundNutrition and food security have been a development priority for decades and remain a major challenge for developing nations like India. Although agriculture is the dominant occupation in India, the rural populations experience poor nutritional outcomes and lag in socio-economic progress. More than half of the Indian women (15–49 years) are anaemic & one-third of the children are stunted. Nutrition-sensitive agricultural practices such as kitchen garden have proven as sustainable methods for reducing undernutrition at affordable costs in different regions. This study aimed to see the relationship between kitchen garden and dietary diversity by using DDS (Dietary Diversity Score) scale in Odisha, India.ObjectivesTo assess the relationship between dietary diversity score (DDS) and backyard kitchen garden & other socio-economic (SE) factors and to explore the enablers & barriers associated with developing a kitchen garden (KG) in rural households of Odisha, India.MethodsThe study used simple random sampling to select 150 participants (WRA group: women of reproductive age) from the eligible household lists. The outcome variable for the investigation was DDS, whereas KG and SE indicators served as predictors/exposure variables. Furthermore, the study used purposive sampling to choose members for FGDs (Focus Group Discussions) to explore enablers and constraints related to growing a KG.ResultsWomen who did not have a household kitchen garden, had poor dietary outcomes, with DDS <5 (OR: 0.163, p = 0.001). Furthermore, a lack of agricultural land lowered DDS (OR: 0.176, p = 0.008) as well. The remaining SE parameters did not demonstrate a statistically significant relationship with DDS/diet quality. The enablers and constraints to building a KG were synthesised from 2 FGDs & further classified into four themes: seasonal fluctuation, local government’s initiatives, men’s engagement, and challenges.ConclusionKitchen garden can improve DDS and nutritional outcomes for the WRA group in rural Odisha. However, the distribution of seeds/saplings and small financial assistance from the local government can help with sustainability, particularly in the lower SE strata.